Nanoparticles Conjugated with Photocleavable Linkers for the Intracellular Delivery of Biomolecules - Jiménez-Balsa, Adrián (2018)
This document is the Accepted Manuscript version of a Published Work that appeared in final form in Bioconjugate Chemistry, copyright © American Chemical Society after peer review and technical editing by the publisher. To access the final edited and published work see https://pubs.acs.org/doi/10.1021/acs.bioconjchem.7b00820